2023
DOI: 10.1044/2023_jslhr-23-00006
|View full text |Cite
|
Sign up to set email alerts
|

Language-Specific Dual-Task Effects After Stroke: A Systematic Review

Abstract: Purpose: The dual-task paradigm has been frequently used to examine stroke-related deficits because it samples behavioral performance under conditions of distraction similar to functioning in real-life environments. This original systematic review synthesizes studies that examined dual-task effects involving spoken language production in adults affected by stroke, including transient ischemic attack (TIA) and poststroke aphasia. Method: Five databases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 102 publications
0
1
0
Order By: Relevance
“…Therefore, dual tasks, especially single leg squat (SLS), are impressive for adults. Previous research has indicated that dual task situations can impair the motor and cognitive function of younger adults and lead to a decline in working memory and executive performance among older adults (20)(21)(22)(23). Various methods have been proposed to prevent and improve dynamic knee valgus.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, dual tasks, especially single leg squat (SLS), are impressive for adults. Previous research has indicated that dual task situations can impair the motor and cognitive function of younger adults and lead to a decline in working memory and executive performance among older adults (20)(21)(22)(23). Various methods have been proposed to prevent and improve dynamic knee valgus.…”
Section: Introductionmentioning
confidence: 99%